Reflectance confocal microscopy and clinical evaluation of a product containing Silybum marianum fruit extract in monotherapy for acne vulgaris treatment: A prospective study - Elisete I. Crocco; Renata O. Alves; Gustavo S. M. Carvalho; Rebeca R. A. Silva; Ricardo S. B. Silva; Karina B. C. V. Calbucci; Ana L. F. Coutinho; Christiano S. Andrade; Juliana C. T. Braga (Wiley, 2024)
Abstract Background Acne is a common pilosebaceous unit chronic inflammatory disease, with a multifactorial pathogenesis. It involves several processes: increased sebum production, alteration of the follicular keratinization process and bacterial colonization by Cutibacterium acnes. Objectives To evaluate the effectiveness of reflectance confocal microscopy (RCM) in evaluating the reduction of mild to severe acne lesions in patients treated with an investigational product containing Silybum marianum fruit extract (SMFE). Methods Subjects previously examined for counting acne lesions were topically treated in the face, with an investigational product containing SMFE in monotherapy over the course of 60 days (n = 31). They were examined for counting acne lesions. Efficacy and quality of life, tolerability, and safety assessments were performed. The infundibular diameter (ID) measurement of normal and acne skin areas was analyzed using RCM. Results The RCM data statistical analysis allowed us to identify two ID patterns, 300-750 µm, with a reduction of 33.33% (p < 0.05) and 900-1050 µm with 73.16% (p < 0.05) reduction after 60 days. The noninflammatory lesions had a mean variation of −44.51% and −67.82% after 30 and 60 days, respectively (t test: p < 0.05 and p < 0.001 after Bonferroni's correction). The inflammatory lesions had a mean variation of −69.31% and −79.40% after 30 and 60 days (t test: p < 0.05 and p = 0.118 after Bonferroni's correction). Conclusions The authors demonstrated the effectiveness of the monotherapy scheme with an investigational product containing SMFE through the statistically significant results obtained by the RCM in acneic and nonacneic skin, in addition to the reduction in the number of noninflammatory at the end of the 60 days of clinical follow‐up. Furthermore, the monotherapy scheme with the investigational product proved safe, with no serious adverse events during the entire clinical study. In summary, the use of RCM proved to be effective in assessing the therapeutic response in patients with moderate to severe acne.